PULMONARY FUNCTION TESTS IN THE SECOND AND THIRD TRIMESTER OF PREGNANCY - SUCHITRA DEOLALIKAR, (International Journal of Pharma and Bio Sciences, 2014)
Health for all has been a goal for all health care delivery systems. Antenatal care is crucial aspect of it.Pregnancy brings in host of biochemical, physiological and anatomical changes.To better understand the respiratory changes, the study of Pulmonary function Test (PFT) in second and third trimester of pregnancy was undertaken. Total 140 women were studied. 35 were control group, and 35 each for second trimester cross sectional, third trimester cross sectional and second trimester longitudinal. For longitudinal study the second trimester patients were successively studied during the third trimester. PFT was done using (a) Vitalograph dry bellows spirometer; and (b) Wright’s mini peak flow meter.Forced Vital Capacity (FVC) showed a significant decrease in second and third trimester of pregnancy compared with control. The other parametersForced Expiratory volume in first second (FEV1), FEV1 (Observed)/FVC (Predicted),Maximum mid expiratory flow rate (MMEFR), Mid expiratory flow rate(MEFR) and Peak flow did not show significant alteration.This study shows that pulmonary functions are largely within normal range.